Current insights on dyslipidaemia management for prevention of atherosclerotic cardiovascular disease: a malaysian perspective - Wan Ahmad, Wan Azman; Rosman, Azhari; Bavanandan, Sunita; Mohamed, Mafauzy; Sk Abdul Kader, Muhamad Ali; Muthusamy, Tamil Selvan; Lam, Kai Huat; Kasim, Sazzli Shahlan; Hoo, Fan Kee; Fegade, Mayuresh; Looi, Zhi Ling; Abdul Rahman, Abdul Rashid (Penerbit Universiti Sains Malaysia, 2023)
Dyslipidaemia is highly prevalent in the Malaysian population and is one of the main risk factors for atherosclerotic cardiovascular disease (ASCVD). Low-density lipoprotein cholesterol (LDL-C) is recognised as the primary target of lipid-lowering therapy to reduce the disease burden of ASCVD. Framingham General CV Risk Score has been validated in the Malaysian population for CV risk assessment. The Clinical Practice Guidelines (CPG) on the management of dyslipidaemia were last updated in 2017. Since its publication, several newer randomised clinical trials have been conducted with their results published in research articles and compared in meta-analysis. This underscores a need to update the previous guidelines to ensure good quality care and treatment for the patients. This review summarises the benefits of achieving LDL-C levels lower than the currently recommended target of < 1.8mmol/L without any safety concerns. In most high and very high-risk individuals, statins are the first line of therapy for dyslipidaemia management. However, certain high-risk individuals are not able to achieve the LDL-C goal as recommended in the guideline even with high-intensity statin therapy. In such individuals, lower LDL-C levels can be achieved by combining the statins with non-statin agents such as ezetimibe and PCSK9 inhibitors. Emerging non-statin lipid-lowering therapies and challenges in dyslipidaemia management are discussed in this article. The review also summarises the recent updates on local and international guidelines for dyslipidaemia management.